Limited persistence of residues and metabolites in fruit and juice following penicillin trunk infusion in citrus affected by Huanglongbing. (November 2019) - McVay, John; Sun, Xiaoan; Jones, Debra; Urbina, Hector; Aldeek, Fadi; Cook, Jo Marie; Jeyaprakash, Ayyamperumal; Hodges, Greg; Smith, Trevor
Abstract: The Florida citrus industry has suffered from Huanglongbing (HLB or citrus greening), a bacterial disease caused by Candidatus Liberibacter asiaticus ( C Las), for almost 13 years with the citrus fruit production declining >70% between 2004 and 2017. With a sense of urgency, scientists with Florida Department of Agriculture and Consumer Services were tasked to seek a possible solution to mitigate the disease. Field trials (2014–16) were conducted to evaluate the effectiveness and environmental detectability of antibiotics used to combat HLB in experimental and commercial groves of Hamlin and Valencia varieties of sweet orange, and grapefruit. Across two year-long experiments, Penicillin G (PCN-G) was administered via trunk infusion into trees and subsequently detected in leaves, fruit and roots within 24 h. PCN-G started degrading 72 h post-infusion, with no detection at day 15 at or above 0.1 mg/L, the minimum level considered lethal to microbes. Reduction of C Las titer, as estimated by qPCR, was observed in treated trees when compared to control trees, and in many cases the rate of titer change over time was greater than that in control trees. Residue analysis of treated fruit for presence of PCN-G and two metabolites through UHPLC/MS confirmed that no PCN-G was present in fruit at harvest time, though metabolites were detected in low concentrations (<1 ppm). We suggest that PCN-G treatment of HLB infected citrus through a single trunk infusion at least 132 days prior to harvest may be a method for control of HLB with potentially minimal impacts on food safety and the environment, though further research will likely lead to improved methods. Highlights: Trunk infusion of penicillin in HLB-affected citrus shows mixed results. Infusions only phytotoxic at high concentrations of penicillin. Penicillin spread to all tissues tested within 24 h following infusion. Only penicillin metabolites, at very low levels, detected in fruit at harvest time.